Original articleAlteration of GSK-3β in the hippocampus and other brain structures after chronic paraquat administration in rats - Songin, Martyna; Ossowska, Krystyna; Kuter, Katarzyna; Strosznajder, Joanna B. (Folia Neuropathologica, 2011)
Systemic exposure of rodents to the herbicide paraquat (PQ) was suggested to reproduce pathological features of Parkinson’s disease. Our recent data showed that long-term PQ administration influenced levels of glycogen synthase kinase 3β (GSK-3β) and its active form phosphorylated on tyrosine 216 in the nigrostriatal system, which may be related to its vulnerability to PQ toxicity. The aim of this study was to analyse selectivity of the toxic effect of PQ after its systemic administration in rats. PQ was administered for 37 weeks and the protein level of total GSK-3β and its active GSK-3β (pY216) form in subcellular fractions of hippocampus, brain cortex and cerebellum was examined. Our data indicated that the long-term administration of PQ significantly decreased the level of both GSK-3β forms in nuclear and cytosolic fractions of hippocampus in rats. In the brain cortex and cerebellum PQ decreased the level of both forms of GSK-3β in the nuclear fraction but increased their levels in mitochondria and in some cases also in the cytosol. The results of the present study indicate that PQ influenced levels and activation of GSK-3β in different brain structures, which may contribute to its toxicity, but on the other hand may suggest development of adaptive, protective mechanisms.